Synthesis, Thermal Behaviours and Crystal Structure of 1,1'-Dioxide-7,7'-bis(terfurazan[3,4-b:3,4'-d:3'',4''-f]azepine) - Huo, Huan; Dong, Jun; Wang, Bo-Zhou; Zhou, Yan-Shui; Ge, Zhong-Xue; Lian, Peng (Asian Journal of Chemistry, 2014)
1,1'-Dioxide-7,7'-bis(terfurazan[3,4-b:3,4'-d:3'',4''-f]azepine) was synthesized from 3,4-bis(4-nitrofurazan-3-yl)furoxan by cyclization and nitration with a yield of 25.7 % and its structure and intermediate were characterized by 1H NMR, 13C NMR, FT-IR and elementary analysis. Its single crystal was obtained and its crystal structure was studied by X-ray single-crystal diffraction analysis. The title compound (C18H12N14O10, Mr = 584.42) crystallizes in trigonal system, P3(2) space group and constituted one 1,1'-dioxide-7,7'-bis(terfurazan[3,4-b:3,4'-d:3'',4''-f]azepine) and two acetone molecules, with a =15.460 (18), b = 15.460 (18), c = 9.603 (11) Å, V = 1988 (4) Å3, Z = 3, Dc = 1.465 g/cm3, l = 0.071073 Å, μ(MoKa) = 0.123 mm-1, F(000) = 894, S = 1.022, R = 0.0720 and wR = 0.1838. In DSC and TG-DTG techniques suggest that there are two main decomposition peaks at 288.7 and 338.7 °C. The results show that the title compound had favorable thermal stability.